Motivasi Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Di Smp Negeri 1 Benteng Kabupaten Indragiri Hilir - hamzah, hamzah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2024)
This research aims to find out the motivation of students in the learning of sports education, sports and health in the State Primary School I Fortress Indragiri Hilir district.This type of research is descriptive and where the site of the research is in the State High School I Fortress, as well as where the population in this study is a total of 17 students as respondents with sampling using the total sampler technique, which obtained samples of a total 17 students. The instruments used in this research are an angket or questionnaire or question using a guttmen scale where data is analyzed using a frequency distribution formula in the form of percentages.From the data analysis results obtained as follows: 1) The level of accessibility for subvariable motivation instrinsic students in learning penjasorkes in SME State I Fortress Indragiri district Hilir of 87,06% with accessibility classification category good. 2).